(E)-5-(2-bromovinyl)-2'-Deoxyuridine in the treatment of experimental herpes simplex keratitis. - Maudgal, P C (1980)
IDU (5-iodo-2'-deoxyuridine), BVDU [(E)-5-(2-bromovinyl)-2'-deoxyuridine] and placebo ointments were studied for their effects on experimental herpes simplex (type 1) keratoconjuncitivitis in rabbits. When treatment was begun 65 h after virus inoculation, both BVDU and IDU prevented development of keratitis. Both BVDU and IDU were also effective in suppressing the severity of conjunctivitis, and in this respect, BVDU proved significantly better than IDU. When treatment was started 110 h after virus inoculation, BVDU proved significantly better than IDU in promoting healing of established keratitis.